Linear modeling and regression for exponential engineering functions by a generalized ordinary least squares method - Abdelhadi, Yaser (International Journal of Engineering and Technology, 2014)
Linear transformations are performed for selected exponential engineering functions. The Optimum values of parameters of the linear model equation that fits the set of experimental or simulated data points are determined by the linear least squares method. The classical and matrix forms of ordinary least squares are illustrated.   Keywords: Exponential Functions; Linear Modeling; Ordinary Least Squares; Parametric Estimation; Regression Steps.